Corporate Responsibility. Maximising Firms’ Positive Social Impact on Society. The Case Study for Deloitte Touche Tohmatsu Limited - Ordenes, Astrid (2011)
In an increasingly connected and globalised world, the expectation on firms to behave in a way that is consistent with its stakeholder’s demands is even higher. Having assumed their role in society as contributors and main actors in the achievement of a sustainable system, global firms struggle at identifying the best opportunities provided by the effective implementation of a CR strategy. Even when resources are available to the consecution of a specific CR programme, the means to achieve the greatest positive impact and returns from the former may be difficult to account or leverage across the units that conform the global firm. The purpose of this research is to identify how a global firm in the professional services industry may achieve to have the greatest impact on society through its CR strategy. For this reason, the signatory CR programme was analysed and interviews with the Deloitte member firms CR representatives from 10 different countries and in the Deloitte network of member firms were conducted that revealed interesting opportunities to achieve a successful global CR platform. Taking into account the competitive context in which the network of Deloitte member firms operate, and advancing the benefits of a CR programme that is defined, delivered and implemented by Deloitte´s professionals, the study developed points toward the positive outcomes derived from a programme that has “talent” as an essential element for the success of the CR platforms.